Study on Optimal Location Determination for 500 kV Extra High Voltage Substation Construction in Paiton Subsystem to Reduce to Transmission Loss - Dede Ridza Diana; Tajuddin Nur; Herlina Herlina; Syamsir Abduh (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Electricity transmission losses are a significant challenge in the Java-Madura-Bali (Jamali) power system, especially in the Paiton subsystem, which is a critical point for power supply to the island of Bali. This study aims to identify the optimal location for the construction of a new Extra High Voltage Substation (GITET) to minimize transmission losses and improve the economic efficiency of the system. The method used is quasi-dynamic power flow simulation with electrical network modeling using PSS/E software integrated with Python, carried out in a time series throughout 2025 at four alternative locations: Watudodol, Jember, Genteng, and Banyuwangi. The simulation results reveal that the construction of GITET in Banyuwangi is technically the most optimal, capable of reducing transmission losses from 420.57 GWh to 94.71 GWh or around 77.5%. Economic analysis shows that the Jember location has the best financial parameters with an IRR of 15.01%, NPV of IDR 4.47 trillion, and a payback period of 9.35 years, even though the reduction in transmission losses is lower than in Banyuwangi. In conclusion, the selection of the GITET location must consider the trade-off between technical efficiency and financial benefits; Banyuwangi excels technically, while Jember is economically optimal, so that a combination of development strategies can maximize the performance of the Jamali electricity system.